Control Strategies of Hybrid Systems WIND/PHOTOVOLTAIC using Advanced Techniques in Maximum Power Point Tracking - Zubaid, Riham Ali (Innovative: International Multidisciplinary Journal of Applied Technology (2995-486X), 2024)
An In this paper, an efficient energy management scheme for Hybrid system is elaborated. The proposed a Hybrid system constrict from Wind turbine and solar energy offers a clean energy solution, The main task of the control loop is to extract and track maximum power from hybrid system with sufficient tracking behavior we suggested a deflection angles of the wind turbine To track the operational point at which the maximum power can be extracted from wind system and generating system under continuously changing climatic conditions, using Bi-Directional Converter for Battery Charging and discharge the battery based on the surplus and deficit of power. When there is an excess of energy, To optimize the power produced in a wind turbine, the speed of the turbine should vary with the wind speed. A simple control method is proposed that will allow an induction machine to run a turbine at its maximum power coefficient a straightforward control technique that is also cost-effective has been presented. Along with modeling results that show the system’s effectiveness, the whole hybrid system is presented. MATLAB/Simulink is used to create a software simulation model.